Analisis Psikologi Tokoh Alie dalam Novel Rumah untuk Alie Karya Lenn Liu Kajian Psikologi Sigmound Freud - Adinda Atiqotuz Zummah; Ahmad Ilzamul Hikam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the psychological dynamics of the character Alie in the novel Rumah untuk Alie by Lenn Liu using Sigmund Freud’s psychoanalytic approach. The focus of the study lies in identifying and interpreting the personality structures of id, ego, and superego, as well as the ego defense mechanisms that emerge as responses to trauma and violence within the family environment. The research method employed is qualitative descriptive, utilizing content analysis techniques on the narrative, dialogue, and monologue of the main character. The results indicate that Alie’s id is manifested in a deep longing for love and protection, the ego functions in adapting and adjusting to the reality of a rejecting family, while the superego is reflected through feelings of guilt and a tendency to accept mistreatment as a form of self-punishment. These findings confirm that traumatic experiences and family pressures significantly influence the development of personality and mental health of the character. This study also highlights the relevance of literary psychology in revealing psychological issues faced by contemporary Indonesian society through literary works.